Indirubin and Indirubin Derivatives for Counteracting Proliferative Diseases. (17th September 2015) - Blažević, Tina; Heiss, Elke H.; Atanasov, Atanas G.; Breuss, Johannes M.; Dirsch, Verena M.; Uhrin, Pavel
Abstract : Indirubin is the active component of Danggui Longhui Wan, a traditional Chinese medicine formulation. The encouraging clinical results from the 1980s obtained in chronic myelocytic leukemia patients treated with indirubin stimulated numerous studies on this compound. These investigations explored the use of indirubin in different types of cancer and reported the synthesis of novel derivatives with improved chemical and pharmacokinetic properties. In this paper, we review the impressive progress that has been made in elucidating the mechanistic understanding of how indirubin and its derivatives affect physiological and pathophysiological processes, mainly by inhibition of cell proliferation and induction of cell death. Furthermore, we survey the therapeutic use of these compounds in combating proliferative diseases such as cancer, restenosis, and psoriasis.